Pengaruh Budget Transparency dan Fiscal Autonomy terhadap Financial Sustainability: Studi Empiris pada Kabupaten dan Kota di Indonesia - Dito Mulda Saferi; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2024)
The purpose of this study is to analyze the effect of budget transparency and fiscal autonomy on the financial sustainability of local governments in Indonesia. The data in this study were sourced from the Local Government Financial Statements obtained from the official website of the local government and the BPK RI website and TPAD data viewed on the official website of the local government. The sample collection method uses a purposive sampling method calculated using the Slovin formula. Hypothesis testing in this study uses multiple linear regression analysis. The results showed that budget transparency has no significant effect on financial sustainability and fiscal autonomy has a significant effect on financial sustainability.